Discourse on LGBT (Lesbian-Gay-Bisexual and Transgender) in Jambi: An Iceberg Phenomenon - Yenti, Zarfina; Kahar, Muhammad Syahrul (International Journal of Psychosocial Rehabilitation, 2020)
Most of the people in Jambi does not really realize the extend on how many people are practicing LGBT. Even though Jambi is a very small city, and many of the people are still devout Muslims and following the norms is still a big tradition, there are still considerable amount of people in Jambi who practice LGBT. To find out how far the reach of LGBTs in Jambi, the researcher decided to conduct a research concentrating in Mauro Jambi, Sungai Penuh, Tanjung Jabung Timur and Kota Jambi. These four districts were chosen because according to the report, these districts are the four districts in Jambi where many of the LGBT communities are concentrated. The research are conducted through in-depth interview, observation and documentation, to find the data on how many people really practice LGBTs and why these people practice LGBT despite the strong possibility of ridicule and oppositions. After the interview were conducted on several people who are in the community, it was found that there are at least five hundreds gays and 200 lesbians ‘listed’ in this community. This number might seem quite small compare to the number of LGBTs around the world or compared to the number of LGBTs in other cities in Indonesia, but it was really worrying since it does not really reflect how many people who are really practicing LGBT in Jambi (or what we called as an iceberg phenomenon). This is also quite alarming since the increase of LGBT community numbers will also increase the possibility of HIV-AIDS infection. The big number shows that there are still many people practicing LGBTs in Jambi despite all the consequences related to it: ridicule, possible rejections, and so many other consequences.